PEMANFAATAN PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS DALAM MENENTUKAN DAERAH RAWAN KEBAKARAN PERMUKIMAN DI KECAMATAN GUGUAK PANJANG KOTA BUKITTINGGI - Mahesha Ramadhini Zolyan; Endah Purwaningsih (JURNAL BUANA, 2020)
This study aims to : 1) determinate the level of vulnerability to fire in District Guguak Panjang. 2) determinate the distribution of residential fire-prone areas in Guguak Panjang District. This type of research is descriptive quantitative with a population of 287 residential block and sample of 36 residential blok. The process used in processing data utilizing geographic information system includes buffering, scoring, overlays and dissolves. The result that obtained is a map of residential fire vulnerability level are divide into three classes: high residential vulnerability level with 21,33 Ha, medium residential fire vulnerability level with 95,97 Ha, and low residential fire vulnerability level with 49,44 Ha. The highest vulnerability distribution is in Bukit Apit Puhun Village and the lowest is in Pakan Kurai Village.